THE ROLE OF HIGHER EDUCATION IN NURTURING SOCIAL ENTREPRENEURSHIP AND IMPACT INNOVATION AMONG UNIVERSITY - Chauhan, Pragya; Satsangi, Prof. Akshay Kumar; Kumar, Dr. Arvind (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The present study attempts to explore the role of higher education institutions in nurturing social entrepreneurship and impact innovation among selected university students. The research evaluates the impact of university efforts on students’ skills and mindset, to understand how universities can better nurture socially conscious entrepreneurs and innovators. This study evaluates how universities support social entrepreneurship and impact innovation, including resource allocation, program diversity, and involvement of students. It also evaluates how these programs impact students’ skills and mindset. It will examine how these initiatives affect students’ skills, mindset, and ability to contribute to society. This research aims to help universities prepare socially conscious entrepreneurs by giving them the necessary tools and mindset for impactful and sustainable innovation and also by measuring factors such as problem-solving abilities, entrepreneurial mindset, and attitudes toward societal challenges. A quantitative method of inquiry is adopted to address the need for research evaluating the effectiveness of prevailing social entrepreneurship and impact innovation initiatives within the selected universities, qualitative insights could enrich the depth of the research findings. Data will be collected through a multistage convenient sampling of respondents from the universities of the Agra region, using a semi-structured questionnaire. This research will help to improve societal well-being by studying the impact of these programs on student’s mindsets and skills. With the help of these programs, higher education can significantly contribute to sustainable development and societal well-being by equipping students with impact innovation skills. As this study was conducted on a limited number of students of universities in Agra (Uttar Pradesh), the results do not claim generalization to other contexts.